Species diversity of zooplankton in coastal waters of Vietnam - family Acartidae (Copepoda) - Cho, Nguyen; Hai Trinh, Truong Si; Lam, Nguyen Ngoc (Academia Journal of Biology, 2012)
Ten species of Acartia were recorded in South Central Coastal waters of Vietnam, in which, 2 species, Acartia sinjiensis and A. tsuensis are newly recorded for zooplankton fauna of Vietnam. Two other species, A. amboinensis and A. bispinosa were listed in previous works without any description and illustration. In this work, these four species are described and illustrated in terms of biology, morphology and their distribution. Identification key of 10 recorded species is also built based on morphological characters.